2019
DOI: 10.1002/ddr.21565
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylaminoparthenolide reduces the incidence of dysplasia and ameliorates a wasting syndrome in HPV16‐transgenic mice

Abstract: The nuclear factor kappa light chain enhancer of activated B cells (NF‐κB) has been implicated in the progression of cancers induced by high‐risk human papillomaviruses (HPV). In cancer patients, NF‐κB is also thought to drive a chronic systemic inflammatory status, leading to cachexia. This study addressed the ability of dimethylaminoparthenolide (DMAPT), a water‐soluble NF‐κB inhibitor, to block the development of HPV‐induced lesions and wasting syndrome in HPV16‐transgenic mice. Mice received DMAPT orally (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…The authors also observed muscle wasting in the Apc Min/+ mice compared to controls [ 39 ]. The results from this study also agree with previous data from our group obtained from HPV16-transgenic female mice [ 14 , 25 ]. It would now be interesting to compare the wasting process in males and females using this mouse strain.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The authors also observed muscle wasting in the Apc Min/+ mice compared to controls [ 39 ]. The results from this study also agree with previous data from our group obtained from HPV16-transgenic female mice [ 14 , 25 ]. It would now be interesting to compare the wasting process in males and females using this mouse strain.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, these mice present HPV16-induced lesions in different locations besides the uterine cervix, and advanced lesions were recently identified in characteristic head-and-neck sites [ 21 , 22 , 23 , 24 ]. Interestingly, the presence of a wasting syndrome in HPV + female mice has also been suggested by our group [ 14 , 25 ].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, the specific characterisitcs of the MA52 strain which allow it to survive in this polluted environment have not yet been described. New drugs are being developed from secondary metabolites in search of less toxic and more effective compounds compared with traditional cancer therapies [13]. Also, some natural products become important nutraceutics with cancer chemopreventive properties [14,15].…”
Section: Introductionmentioning
confidence: 99%